Implementation Performance of Specific and Sensitive Nutrition Interventions for Stunting Control in Kupang Regency, Indonesia: A Cross-Sectional Study - Florentianus Tat; Muhamad Satria Mandala Pua Upa; Mariana Ngundju Awang; Riny Pujiyanti; Emanuel Gerald Alan Rahmat; Joel Rey U. Acob (Poltekkes Kemenkes Palu, 2026)
Background: Stunting remains a significant public health concern in East Nusa Tenggara Province, particularly in Kupang Regency. Despite nationally mandated specific and sensitive nutrition interventions, evidence on local implementation performance is limited. This study assessed the implementation status of stunting control programs in Kupang Regency. Methods: A cross-sectional study was conducted among 88 mothers of children who received stunting interventions. Data were collected using structured questionnaires and interviews covering 15 specific and 12 sensitive nutrition indicators. Implementation performance was measured using mean percentage scores. Data were analyzed descriptively (frequency, percentage, and mean). Results: Specific nutrition interventions achieved a mean implementation score of 68.40% across 15 indicators, indicating incomplete coverage of targeted services. Sensitive nutrition interventions showed a comparable mean score of 68.65% across 12 indicators, reflecting suboptimal multisectoral integration at the household level. Conclusion: The implementation of stunting control programs in Kupang Regency remains suboptimal across both intervention domains. Strengthening coordination, service delivery, and community-based nutrition education is essential to improve program performance and accelerate stunting reduction.